Akselerasi Transisi Energi di Sektor Ketenagalistrikan melalui Redesain Insentif Perpajakan - I Putu Hendy Bimantara Dinata; Bhima Chandra Bhuana; Muhammad Taufiq Badruzzuhad; Amrie Firmansyah (Juara: Jurnal Riset Akuntansi, 2023)
The government of the Republic of Indonesia has provided numerous incentives and subsidies to encourage the achievement of Indonesia's target and commitment to achieve net zero emission by 2060, even for battery-based electric motor vehicles. However, Indonesia's journey in the energy transition to renewable energy, especially in the electricity generation sector, has encountered turbulence and failures to achieve targets. This research aims to determine how tax incentives can be optimized to catalyze the increase in the national renewable energy mix in electricity generation. This research uses a qualitative approach using the literature review method by collecting data on various countries' tax incentive policies, then analyzing it with a descriptive method. Our main finding is that the government needs to redesign tax incentives for the electricity sector to create contrast and increase attractiveness for investors to develop renewable energy. It can be conducted by reducing tax incentives for non-renewable energy-based power plants and increasing tax incentives for renewable energy-based power plants. We suggest the government implement tax allowance schemes for the installation and maintenance process, increased tax deduction schemes, enhanced capital allowance schemes, reduced threshold requirements for obtaining tax holidays, and productionÂ taxÂ credits.